The Behaviour of As(III) and As(V) During the Precipitation of Alunite at 98°C - Alba Sunyer; J. E. Dutrizac (Canadian Institute of Mining, Metallurgy and Petroleum, 2011)
The factors affecting the precipitation of arsenic-free alunite (KAl3(SO4)2(OH)6) were investigated in a series of laboratory experiments. Although the amount of alunite precipitated increased with increasing retention time, temperature, solution pH and the concentrations of Al(SO4)1.5 or K2SO4, the composition of the products remained nearly constant. The preferred conditions identified for the precipitation of arsenic-free alunite were then used to assess the behaviour As(III) and As(V) during alunite precipitation at 98°C. Increasing additions of As(III), as NaAsO2 or As2O3, resulted in a slight increase in the amount of precipitate formed at pH 2.80. However, X-ray diffraction analysis showed all the precipitates to be alunite, and <0.2% As(III) was detected in the products. In contrast, increasing additions of As(V), as KH2AsO4 or As2O5, resulted in significant increases in the amount of precipitate formed at pH 2.80 or 3.00. Furthermore, the arsenate (AsO43-) contents of the precipitates increased up to 15%, and the sulphate contents decreased, as the As(V) concentration of the synthesis solution increased from 0 to 9 g/L. X-ray diffraction analysis of the products detected only alunite, but there was a progressive expansion of the alunite cell with increasing arsenate content. The implication is that arsenate substitutes for sulphate in the alunite structure. Preliminary observations on the environmental stability of the arsenate-bearing alunite using the TCLP protocol gave solubilities <0.4 mg/L from a precipitate containing 8.5% AsO4 and 7.8 mg/L from a product containing 19.5% AsO4. Thus, it appears that alunites containing less than -10% AsO4 would be an acceptable vehicle for the disposal of arsenic from hydrometallurgical processing solutions.